2016
DOI: 10.1063/1.4969051
|View full text |Cite
|
Sign up to set email alerts
|

The influence of capping layers on pore formation in Ge during ion implantation

Abstract: Ion induced porosity in Ge has been investigated with and without a cap layer for two ion species, Ge and Sn, with respect to ion fluence and temperature. Results without a cap are consistent with a previous work in terms of an observed ion fluence and temperature dependence of porosity, but with a clear ion species effect where heavier Sn ions induce porosity at lower temperature (and fluence) than Ge. The effect of a cap layer is to suppress porosity for both Sn and Ge at lower temperatures but in different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 26 publications
3
8
0
Order By: Relevance
“…Noticeably, the Ge layer in this study does not develop into a porous structure as observed for an implant at this dose and ion energies of several hundred keV. We have mentioned that porosity in Ge consistently occurs for the implant dose > 2 − 3 • 10 15 cm −2 at room temperature for the medium energy regime [10,13,14] and for the high energy regime [18,19].…”
supporting
confidence: 56%
See 2 more Smart Citations
“…Noticeably, the Ge layer in this study does not develop into a porous structure as observed for an implant at this dose and ion energies of several hundred keV. We have mentioned that porosity in Ge consistently occurs for the implant dose > 2 − 3 • 10 15 cm −2 at room temperature for the medium energy regime [10,13,14] and for the high energy regime [18,19].…”
supporting
confidence: 56%
“…Therefore, the characteristics of the morphology are different at medium energies. Indeed, under ion irradiation at hundreds of keV, Ge shows different modifications from shallow pits [7] to sponge-like structures [8][9][10]. Using a 280 keV 209 Bi ion beam, Appleton et al were the first to report a porosity effect in Ge implanted at the dose of ~4 • 10 15 cm −2 at room temperature [8,11,12].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Above À50 C, the effectiveness of the cap completely diminishes, particularly for heavy implant species such as Sn or Sb. 23 Further investigation of the samples was conducted by using electron microscopy analysis (SEM and TEM) on selected samples of interest. In Fig.…”
mentioning
confidence: 99%
“…However, it may be related to the confining effect of the cap in suppressing ion-induced vacancy migration and agglomeration at the surface. 23 Further studies would be needed to resolve this issue.…”
mentioning
confidence: 99%